Is Covid-19 "the great leveler"?: the critical role of social identity in lockdown-induced job losses - Deshpande, Ashwini; Ramachandran, Rajesh (GLO discussion paper, 2020)
Using nationally representative panel data for 21,799 individuals between May 2018 and April 2020, this paper investigates whether the Covid-19 pandemic was indeed a "Great Leveler" in the sense that it imposed similar and equivalent labour market shocks on different caste groups. We find that while all caste groups lost jobs in the first month of the lockdown, the job losses for lowest-ranked caste are greater by factor of three. The data shows that the disproportionate effects stems from lower levels of human capital and over-representation in vulnerable jobs for the lowest ranked caste groups in the country.